Effect of inflammation on endothelial cells induced by poly-L-lactic acid degradation in vitro and in vivo. Issue 15 (13th October 2018) - Chen, Dongping; Su, Zhaobing; Weng, Linsheng; Cao, Longbin; Chen, Can; Zeng, Sufen; Zhang, Suzhen; Wu, Tim; Hu, Qiang; Xiao, Jianmin
Abstract: As a promising candidate, biodegradable Poly-L-lactic Acid (PLLA) has been extensively used in coronary artery stents. In our previous reports, PLLA stents implanted in porcine coronary arteries showed safety without stent thrombosis. However, inflammatory responses were observed, which needed further study. In this study, human aortic endothelial cells (HAEC) were treated with different volume percentages of extract of pre-degraded PLLA (extract of PLLA) in vitro, and the cell growth curve and morphological changes were examined. The expression of inflammatory cytokines such as NF-κB, VEGF and VCAM-1 were also observed by ELISA. In addition, PLLA stent was implanted in porcine coronary artery to examine morphological changes, functional marker eNOS and inflammatory responses. The extract of PLLA caused significant growth inhibition and release of NF-κB, VEGF and VCAM-1 in HAEC with volume percentage-dependence. Although re-endothelialization and expression of eNOS was observed, expression of NF-κB and lymphocytes surrounding PLLA were also found after PLLA stents were implanted in the artery. This study demonstrated the effects of inflammation on endothelial cells induced by PLLA degradation in vitro and showed the inflammation in vivo, suggesting that anti-inflammatory strategy is necessary for PLLA stent implantation in the artery.